2014
DOI: 10.1021/ja5065075
|View full text |Cite
|
Sign up to set email alerts
|

Network Reorganization of Dynamic Covalent Polymer Gels with Exchangeable Diarylbibenzofuranone at Ambient Temperature

Abstract: Reversible bonds and interactions have been utilized to build stimuli-responsive and reorganizable polymer networks that show recyclability, plasticity, and self-healing. In addition, reorganization of polymer gels at ambient temperature, such as room or body temperature, is expected to lead to several biomedical applications. Although these stimuli-responsive properties originate from the reorganization of the polymer networks, not such microscopic structural changes but instead only macroscopic properties ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 36 publications
2
76
0
Order By: Relevance
“…[28] AFM observations of single-chain polystyrene particles revealed that the morphology changed to as maller coil size when the polymer solution was frozen, but recovered to that observed before freezing by heating to 100 8 8C. [33][34][35][36] Theradicals are blue-colored and show greatly reduced reactivity toward oxygen. [29,30] Somer eports have also indicated that freezing ap oly(ethylene oxide) solution induces au nique polymer chain conformation, which is only found under elongation force field.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…[28] AFM observations of single-chain polystyrene particles revealed that the morphology changed to as maller coil size when the polymer solution was frozen, but recovered to that observed before freezing by heating to 100 8 8C. [33][34][35][36] Theradicals are blue-colored and show greatly reduced reactivity toward oxygen. [29,30] Somer eports have also indicated that freezing ap oly(ethylene oxide) solution induces au nique polymer chain conformation, which is only found under elongation force field.…”
mentioning
confidence: 80%
“…[33][34][35][36] Theradicals are blue-colored and show greatly reduced reactivity toward oxygen. DABBF and its corresponding radicals are in equilibrium at room temperature without the formation of by-products (reversible), though the amount of radicals formed is quite small.…”
mentioning
confidence: 89%
“…This may be due to network expansion and elution of cyclic oligomers formed through bond exchange between the DABBF linkages. 69 We utilized this property to investigate the polymer structure via 1 H NMR in CDCl 3 solution ( Figure S3). The composition ratio was determined to be TEA/DABBF/HDI/ PPG = 1/1.40/5.20/2.30, which was largely similar to that of the reaction mixture (1/1.5/6/3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The dynamic nature of the polymer also allowed introduction of a chain transfer agent to control polymerization or end group functionalization. Imato et al demonstrated that the reversible dissociation of a diarylbibenzo‐furanone into two carbon‐centered radicals can be used to create polyurethane networks that can undergo exchange at ambient temperature . The self‐healing behavior was evaluated on the macroscopic level by mechanical testing (Fig.…”
Section: Othersmentioning
confidence: 99%